Arbitration in construction industry in Malaysia / Nor Azmi Bakhary and Azmi Othman - Bakhary, Nor Azmi; Othman, Azmi (Research Management Institute (RMI), 2008)
Disputes in construction industry are normal and sometimes cannot be avoided. Disputes arise from the interpretation and/or application of any part of building or engineering contract documents that are ambiguous, unplanned and conflicting at any time during the execution of the contract. There are many methods/techniques have been introduced in order to resolve the disputes and arbitration is one of the popular recommended method. This study examines the concept of arbitration and its acceptance by the Malaysia construction industry. Questionnaires have been sent to the selected contractors to collect information, data and views regarding to arbitration process, procedures and award. The survey reveals that arbitration still fails to impress Malaysian contractors. Lengthy time and high expenses are the common reasons given. Improvement must be made in order to improve the efficiency and the effectiveness of arbitration. New techniques of dispute resolution can be introduced by taking into account the problems existing in the recent techniques available and come out with better techniques that can guaranty satisfaction to the users.